2015
DOI: 10.1093/jjco/hyv174
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for survival and correlation to toxicity in advanced Stage III non-small cell lung cancer patients with concurrent chemoradiation

Abstract: Objective: Concurrent chemoradiotherapy is the standard treatment for locally advanced Stage III non-small cell lung cancer in patients with a good performance status and minimal weight loss. This study aimed to define subgroups with different survival outcomes and identify correlations with the radiation-related toxicities. Methods: We retrospectively reviewed 381 locally advanced Stage III non-small cell lung cancer patients with a good performance status or weight loss of <10% who received concurrent chemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Gandara DR and Chansky K demonstrated that cisplatin and S-1 with concurrent TRT in unresectable stage III NSCLC patients undergone grade 3/4 leukopenia in 50%, neutropenia in 25%, pneumonitis in 26% of patients [26]. A Japanese study reported that cisplatin or carboplatin, paclitaxel and docetaxel with concurrent RT resulted in an incidence of 13% acute grade 3/4 pneumonitis toxicity and 13% grade 3/4 esophageal toxicity in stage III elderly NSCLC patients [27]. The consequences of our trial are considered remarkably lower toxicity than these three investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Gandara DR and Chansky K demonstrated that cisplatin and S-1 with concurrent TRT in unresectable stage III NSCLC patients undergone grade 3/4 leukopenia in 50%, neutropenia in 25%, pneumonitis in 26% of patients [26]. A Japanese study reported that cisplatin or carboplatin, paclitaxel and docetaxel with concurrent RT resulted in an incidence of 13% acute grade 3/4 pneumonitis toxicity and 13% grade 3/4 esophageal toxicity in stage III elderly NSCLC patients [27]. The consequences of our trial are considered remarkably lower toxicity than these three investigations.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study showed that age >75 years (p = 0.009), diffusion lung capacity for carbon monoxide (DL CO ) ≤80% (p = 0.011), and gross tumor volume (GTV) ≥ 100 cm 3 (p = 0.001) were statistically significant factors. Severe esophageal and lung toxicity and interruption of RT were more frequent in patients with multiple adverse prognostic factors [14]. …”
Section: Patient Fitness and Age Restrictions For Ccrtmentioning
confidence: 99%
“…There remain controversial results regarding age factors (Table 3). Several studies have reported that CCRT could benefit appropriately selected elderly patients [14,16]. In a subgroup analysis of elderly patients (≥75 years), the median survival time was 31 months for those with adequate pulmonary function (DL CO > 80%), with a small tumor volume (GTV < 100 cm 3 ).…”
Section: Patient Fitness and Age Restrictions For Ccrtmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] However, there is a need for more effective and less toxic regimens as the 5-year survival rates remain low (approximately 14% for stage IIIA and 5% for stage IIIB NSCLC). 2,6 In the PROCLAIM phase 3 trial, concurrent pemetrexed plus cisplatin and thoracic radiotherapy (TRT) followed by consolidation pemetrexed (arm A) in stage IIIA/B inoperable NSCLC did not show superior survival versus a standard concurrent chemoradiotherapy with consolidation (etoposide; arm B). 7 Both treatment arms had longer than expected median overall survival (OS) compared to historical data.…”
Section: Introductionmentioning
confidence: 99%